2005
DOI: 10.1186/1744-859x-4-13
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Obstructive Sleep Apnea (OSA)

Abstract: For over two decades clinical studies have been conducted which suggest the existence of a relationship between depression and Obstructive Sleep Apnea (OSA). Recently, Ohayon underscored the evidence for a link between these two disorders in the general population, showing that 800 out of 100,000 individuals had both, a breathing-related sleep disorder and a major depressive disorder, with up to 20% of the subjects presenting with one of these disorders also having the other. In some populations, depending on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(85 citation statements)
references
References 82 publications
2
81
0
2
Order By: Relevance
“…One important line of research builds upon findings from several large-scale epidemiological studies, which have demonstrated that approximately 20% of depressed patients exhibit a frequently undiagnosed sleep-disordered breathing, mostly obstructive sleep apnea [28,29]. This goes in line with a large number of reports which have gathered data linking metabolic syndrome and, most importantly, obesity and diabetes or insulin resistance, together with elevated inflammatory markers, to both sleep-disordered breathing and depression [30][31][32][33][34][35][36].…”
Section: Eds and Depressionmentioning
confidence: 88%
“…One important line of research builds upon findings from several large-scale epidemiological studies, which have demonstrated that approximately 20% of depressed patients exhibit a frequently undiagnosed sleep-disordered breathing, mostly obstructive sleep apnea [28,29]. This goes in line with a large number of reports which have gathered data linking metabolic syndrome and, most importantly, obesity and diabetes or insulin resistance, together with elevated inflammatory markers, to both sleep-disordered breathing and depression [30][31][32][33][34][35][36].…”
Section: Eds and Depressionmentioning
confidence: 88%
“…However, a decrease in libido and excessive fatigue [60] associated with the common symptoms found in OSA patients (i.e., morning tiredness, excessive daytime sleepiness, and mood changes [61]) likely represent a psychologic component involved in the pathogenesis of ED in OSA.…”
Section: Psychological Mechanismsmentioning
confidence: 99%
“…Covariate-adjusted remission rates were 15.5% for lower-dose and 28.3% for higher-dose exercise augmentation, leading to an NNT of 7.8. Trivedi et al 48 point out that remission rates with exercise are comparable to those seen with an SSRI/bupropion combination and that their results are within the range of findings that warrant change in clinical practice. According to Dr Trivedi, for a person weighing about 80 or 90 kg, about 1,200-1,400 calories of energy expenditure per week is needed to see an effect.…”
Section: Nonpharmacologic Strategiesmentioning
confidence: 98%
“…The participants agreed that physical exercise can be an effective adjunct, and Dr Weisler pointed to Dr Trivedi's contributions in this area. In a sample of sedentary individuals with SSRI-resistant MDD, Trivedi and colleagues 48 compared two 12-week exercise interventions with energy expenditures equivalent to walking 210 minutes per week at 4 miles per hour or 75 minutes per week at 3 miles per hour. Covariate-adjusted remission rates were 15.5% for lower-dose and 28.3% for higher-dose exercise augmentation, leading to an NNT of 7.8.…”
Section: Nonpharmacologic Strategiesmentioning
confidence: 99%